The Metaverse Is Geospatial: A System Model Architecture Integrating Spatial Computing, Digital Twins, and Virtual Worlds - Theofilos Papadopoulos; Konstantinos Evangelidis; Theodore H. Kaskalis; Georgios Evangelidis (ISPRS International Journal of Geo-Information)
Virtual geographic environments long simulated real-world scenarios in urban planning, monument preservation, city infrastructure management, education, and entertainment. Their web-based visualisation and distribution made these environments widely accessible. However, many systems remain static, lacking real-time data integration and multi-user collaboration, while virtual worlds designed for the Metaverse emphasise dynamic interaction yet often omit essential geospatial context. Bridging this gap is critical for advancing virtual geographic environments into the next generation. In this paper, we present a modular system architecture for applications demonstrating geospatial virtual worlds over the web. Our goal is to provide a generic, well-structured framework that exposes the essential classes and interfaces needed for building 3D virtual worlds with geospatial data at their core. Our work focuses on defining specific geospatial components, methods, classes, and interfaces that form the foundation of a modern geospatial virtual environment in the Metaverse era. The proposed architecture is organised into three layers: access, world, and integration, which together enable accurate mapping and integration of real-time sensor data, digital twin synchronisation, and support for location-based services. Our analysis reveals that while most current solutions excel in either multi-user interaction or geospatial data management, they rarely combine both. In contrast, our model delivers enhanced geospatial focus, real-time collaboration, and interoperability between physical and digital realms. Overall, this work lays a solid foundation for future innovations in creating immersive, interactive, and geospatially grounded virtual experiences over the web, marking an important step in the evolution of virtual geographic environments for the Metaverse era.